Genes required for growth at high hydrostatic pressure in Escherichia coli K-12 identified by genome-wide screening. - S Lucas Black (Public Library of Science (PLoS), 2013)
Despite the fact that much of the global microbial biosphere is believed to exist in high pressure environments, the effects of hydrostatic pressure on microbial physiology remain poorly understood. We use a genome-wide screening approach, combined with a novel high-throughput high-pressure cell culture method, to investigate the effects of hydrostatic pressure on microbial physiology in vivo. The Keio collection of single-gene deletion mutants in Escherichia coli K-12 was screened for growth at a range of pressures from 0.1 MPa to 60 MPa. This led to the identification of 6 genes, rodZ, holC, priA, dnaT, dedD and tatC, whose products were required for growth at 30 MPa and a further 3 genes, tolB, rffT and iscS, whose products were required for growth at 40 MPa. Our results support the view that the effects of pressure on cell physiology are pleiotropic, with DNA replication, cell division, the cytoskeleton and cell envelope physiology all being potential failure points for cell physiology during growth at elevated pressure.